2015
DOI: 10.19056/ijmdsjssmes/2015/v4i1/79964
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Imaging: A Pictorial Essay

Abstract: The major salivary glands are parotid, submandibular and sublingual glands. Imaging has an important role to play in detection, diagnosis, aiding biopsy and differentiating benign from malignant pathology. The traditional imaging modalities include plain radiography and sialography. With the advent of modern imaging methods like high resolution ultrasound with color doppler, contrast enhanced CT, MRI and MR sialography, the imaging has become increasingly reliable in making a confident diagnosis. A wide variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Thereafter, four months plus, patch distortions of nearly all acini are observable and few serous cells remain while the ducts and lobules undergo fibrosis. 34 Atri et al, 22 observed that the salivary glands can tolerate ionizing radiation dose in the range of 32Gy to 46Gy. However, curative doses may range up to 60Gy and sometimes more.…”
Section: External Beam Radiation Therapy Of Head and Neck Cancers Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Thereafter, four months plus, patch distortions of nearly all acini are observable and few serous cells remain while the ducts and lobules undergo fibrosis. 34 Atri et al, 22 observed that the salivary glands can tolerate ionizing radiation dose in the range of 32Gy to 46Gy. However, curative doses may range up to 60Gy and sometimes more.…”
Section: External Beam Radiation Therapy Of Head and Neck Cancers Andmentioning
confidence: 99%
“…Medical imaging provides us with a suitable procedure because salivary glands are responsive to imaging using MRI, CT, US and radionuclide imaging. [26][27][28][29][30][31][32][33][34] However, it is important that the best imaging modality be determined.…”
Section: External Beam Radiation Therapy Of Head and Neck Cancers Andmentioning
confidence: 99%
See 3 more Smart Citations